ADHD and Thyroid Hormone Resistance - J Gordon Millichap (Pediatric Neurology Briefs)
The presence and severity of attention deficit-hyperactivity disorder (ADHD) in 104 members of 18 families with a history of generalized resistance to thyroid hormone were evaluated at the National Institutes of Health, Bethesda, MD, using structured interviews.